Strengthening the Capability of Elderly Cadres in Utilizing EMS (Emergency Medical System) PSC (Public Safety Center) 119 and Stroke Prevention Efforts Through the RiSS (Risk Stroke Score) Stroke Calculation Application in Karangsoko Village in the Trengg - Yuswantoro, Edi; Ixora, Ixora; Christiani, Mimik (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2026)
Karangsoko Village in Trenggalek Regency has experienced an increasing prevalence of stroke and hypertension, which is exacerbated by limited community awareness of early stroke detection and underutilization of emergency medical services, resulting in delayed treatment. This community service program aimed to improve the knowledge and skills of elderly community health workers (cadres) in early stroke detection, utilization of the Public Safety Center (PSC) 119 emergency system, and application of the Risk Stroke Score (RiSS) as a community-based prevention tool. The program was conducted through health education sessions, hands-on training on the RiSS application, simulation of early stroke detection and emergency referral procedures, and evaluation using pre- and post-tests. The results showed a significant improvement in cadres’ knowledge and competencies, with all participants achieving a “good” category after the intervention. Cadres were able to independently assess stroke risk using the RiSS application and demonstrated increased preparedness in activating PSC 119 during emergency situations. This program effectively strengthened the role of elderly cadres in community-based stroke prevention and emergency response. It is recommended that this program be expanded to a wider community and disseminated through scientific publications to support sustainable stroke prevention efforts.